The study on the effects of lifting parameters on metabolic energy consumption of manual lifting works - Iqbal, Mohammad; Hassan, Azmi; Putera, Adi (NIOSH Malaysia, 2005)
An experiment was conducted to study the effects of lifting parameters on metabolic energy consumed by Malaysian workers while providing manual lifting tasks. Four parameters have been considered: weight of load, lifting posture, level of lifting and gender of the worker. Three load weight, three lifting level and two lifting posture were investigated for both male and female subjects. Three male and four female workers (mean ages of 23.67 and 22 years old, respectively) performed the experiment. The experiments were conducted at National Institute of Occupational Safety and Health (NIOSH) Malaysia. The metabolic energy was measured with a Metabolic Energy Measurement Device (Cosmed, Model K4-b2) and the subject's heart rate was monitored with a Heart Rate Monitor (Polar Model S610). The results of the experiments show that the load weight, working posture, level of lifting and gender of the worker had a significant effect on the metabolic energy expenditure. It was found that the metabolic energy expenditure increase as load weight and lifting level increase for both male and female subjects. Compare to stoop lift, squat lift needs more metabolic energy for all of the lifting tasks. For the future work, the results of the experiment will be further analyzed in order to find the mathematical model for metabolic energy of manual lifting task for Malaysian workers.